2011
DOI: 10.1007/s00405-011-1800-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of obstructive sleep apnea and age on daytime blood pressure

Abstract: Epidemiologic studies have shown obstructive sleep apnea (OSA) is an independent risk factor for systemic hypertension. The prevalence of systemic hypertension also increases gradually with age. The purpose of this study was to assess the combined effect of OSA and age on daytime blood pressure. Patients who received nocturnal polysomnography in Tainan Municipal Hospital were invited between October 2008 and February 2010. Daytime blood pressure was measured. Participants were classified into three groups: non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…These population characteristics have individually been associated with higher therapeutic effects of CPAP on BP. 4,20,29,30 Age and OSA interact as risk factors for hypertension 31 : the importance of age as an effect modifier of treatment response is illustrated in this study; that is, older men showed greater OSA treatment-related response in both systolic and diastolic BP. The effect size (Cohen's d for repeated measures) when considered by type of treatment and race varied from small to large, indi- cating that type of treatment and race may also be significant determinants of HTE.…”
Section: Discussionmentioning
confidence: 67%
“…These population characteristics have individually been associated with higher therapeutic effects of CPAP on BP. 4,20,29,30 Age and OSA interact as risk factors for hypertension 31 : the importance of age as an effect modifier of treatment response is illustrated in this study; that is, older men showed greater OSA treatment-related response in both systolic and diastolic BP. The effect size (Cohen's d for repeated measures) when considered by type of treatment and race varied from small to large, indi- cating that type of treatment and race may also be significant determinants of HTE.…”
Section: Discussionmentioning
confidence: 67%
“…It was a great pleasure that we have read the article entitled ''Combined effect of obstructive sleep apnea and age on daytime blood pressure'' by Chao et al [1]. After reading the article, we benefited a lot from it.…”
mentioning
confidence: 99%